Time trends and spatial distribution of class A and B notifying infectious diseases in China: a national epidemiological study for 18 years - Chenxi Zhang; Haiyin Wang; Chunlin Jin (All Life)
This study aimed to investigate the prevalence and social determinants of class A and B infectious diseases in mainland China. We collected data on these infectious diseases from the China Health Statistics Yearbook database, including all diagnosed cases in mainland China from January 2004 through December 2021. Over this period, a total of 57,478,155 Class A and B infectious disease cases were documented, demonstrating an overall decline in incidence. Using a two-way fixed effects model, we found that an increase in the percentage of the illiterate population relative to the total population (P < 0.05), the density of paved roads per capita (P < 0.001), and the accessibility of family health service personnel per capita (P < 0.01) were associated with higher disease incidence. In contrast, enhanced access to public green space per capita (P < 0.001) and increased number of public transportation vehicles per 10,000 inhabitants (P < 0.05) were associated reduced disease incidence. These findings underscore the profound impact of social determinants, such as literacy rates, family health service availability, and urban infrastructure, on the management and control of infectious diseases. Key policy highlights The incidence and social determinants of class A and B infectious diseases in mainland China were investigated. Data were collected from the China Health Statistics Yearbook database, including all diagnosed cases. Between 2004 and 2021, the overall incidence of Class A and Class B infectious diseases in China declined. The annual incidence of hepatitis, tuberculosis, syphilis, bacteriophage, and amebic dysentery, and four major diseases with the highest incidence rates gradually stabilized over time. Social determinants, such as illiteracy rates, family health services, public green spaces, public transportation, and paved road areas, may have influence in the effective control of infectious diseases.